The Diminishing Importance of Primary Site Identification in Cancer of Unknown Primary: A Canadian Single-Center Experience - Wong, Boaz; Vickers, Michael M.; Wheatley-Price, Paul (Frontiers in Oncology, 2021)
Background: Cancer of unknown primary (CUP) describes patients with metastatic disease without an identified primary tumour site. Successful diagnosis and treatment of these patients remains difficult. Published guidelines on CUP have highlighted “favorable” subtype groups. We investigated a series of CUP patients to review adherence to guidelines, and identification of primary cancers or “favorable” subtypes. Methods: Patients with histologically confirmed CUP at an academic institution from 2012 - 2018 were identified. Patient demographics, tumour presentation, diagnostic work-up and treatment information were retrospectively collected from electronic data records for descriptive analysis and compared to published clinical guidelines. The primary endpoint was the proportion of patients where the primary site was identified. Multivariable logistic regression models were used to identify factors associated with primary site identification. Kaplan-Meier survival curves were used to determine factors associated with poorer OS. Results: 305 patients were included with a median follow-up time of 4.3 months. Primary tumour sites were identified in 109 patients (37.5%), which was most commonly lung cancer (33%). Statistical analyses did not identify any demographic or initial presentation factors associated with identifying the primary or not. More diagnostic tests did not increase the likelihood of primary site identification (P=0.44). Patients with an identified primary did not have longer OS than other patients (median 5.2 vs. 4.7 months, P=0.47). 57 patients (18.7%) who had a defined “favorable” subtype experienced superior OS (36.6 vs. 3.8 months; P<0.0001). Further, patients with good prognostic status who followed published treatment guidelines had longer OS (17.6 vs. 13.2 months; P=0.04). Conclusions: CUP remains a difficult cancer to diagnose and treat. These results suggest identifying the primary has less impact than anticipated, but particular efforts to identify patients with “favorable” subtypes of CUP is important prognostically.